The Duration of Combined Oral Contraceptive Use on The Incidence of Melasme - Faza, Faza Nabila (Rifa'Institute, 2025)
Introduction: Melasma is a common problem experienced by women. The cause of melasma is not only age but also the use of contraceptives. Melasma is a frequent complaint among birth control users because it significantly affects their appearance and aesthetics. Objective: The purpose of this study was to determine whether the duration of combined oral contraceptive use affects the incidence of melasma. Method: This study used a cross-sectional approach. The sample size of 55 users. The study was conducted from May to July 2025 in the Gending Community Health Center area, Gresik. Data collection used a questionnaire directed to respondents. Data analysis used the chi-square test. Result and discussion: The results of the study showed that there was an effect of the length of use of combined oral contraceptives on the incidence of melasma with a significance value of 0.003. Conclusion: The duration of combined oral contraceptive use can affect the incidence of melasma in women of childbearing age and those who have used it for more than 2 years.